Renal Denervation: A Practical Guide for Health Professionals Managing Hypertension - Schmieder, Roland; Burnier, Michel; East, Cara; Tsioufis, Konstantinos; Delaney, Sean (Interventional Cardiology (London), 2023)
Growing evidence demonstrates the suitability of renal denervation in a broad population of patients; however, questions remain over its suitability and practical implementation. Given the rapidity of emerging data, this has been a challenging field for potential adopters to navigate. The purpose of this article is twofold: to provide navigation through emerging clinical data and evolving guidance; and to provide physicians with practical, evidence-based advice for identifying eligible patients and providing appropriate management in the pre- and postintervention settings. Although many of these recommendations are based on existing published guidance documents, we reflect equally on our own experiences of using this technology.
CRIS-Team Scopus Importer:2023-04-07
Keywords: antihypertensive; blood pressure control; cardiovascular risk; Hypertension; recommendations; renal denervation